THE PROBLEM OF USE OF MUSICAL THERAPY FOR REGULATION BY MENTAL STATE AND OPERABILITY OF THE PERSON - Halajyan, W. M. (Modern Psychology, 2025)
The article analyzes the function of musical influence and musical therapy in the process of regulation by the mental state and capacity for work of the person. In this study discusses different aspects of musical therapy, types, as well as some studies on the therapeutic and regulatory functions of music. The idea is that music therapy can be an effective way to enhance and activate the working capacity of a person and reduce professional exhaustion.